Research on the thermal-mechanical interaction of the defect evolution and surface generation during the drilling of thermoplastic composites - Xunxun Zhang; Jielin Chen; Han Li; Linjia Zhu; Yaya Zhou; Ronghua Yan; Ruhao Tao; Liangliang Lin; Qinglong An; Weiwei Ming; Ming Chen (Journal of Materials Research and Technology)
Carbon fiber-reinforced thermoplastic composites (CFRTPs) are increasingly adopted in the aerospace and automotive industries due to their recyclability and superior toughness. However, existing studies predominantly focus on machining metrics, with limited insights into the thermal-mechanical interactions in CFRTPs cutting, particularly the matrix properties transitions. This study conducts comparative drilling experiments on thermoplastic (CF/PEKK, CF/PPS) and thermosetting (CF/Epoxy) composites. This study is the first systematic comparison of the thermal-mechanical interaction behavior of carbon fiber-reinforced PEKK/PPS/Epoxy in drilling and the nonlinear effect of the glass transition temperature (Tg) on cutting force. Thrust forces, drilling temperatures, delamination damage, surface microstructure and roughness, and chip morphology are systematically analyzed. Chip temperatures in CF/Epoxy remain below tool temperatures throughout drilling, while CFRTPs exhibit chip temperatures exceeding tool temperatures by 5 %–36 % during initial stages. The machined surface of CFRTPs exhibits obvious matrix smears, including matrix plastic flow as well as matrix melting and cooling-induced surface reformation, resulting in lower delamination damage (Fda) and surface roughness (Sa). The Fda ratios for CF/Epoxy, CF/PEKK, and CF/PPS are 5:1.8:1, while Sa ratios are 2.5:1.1:1. Statistical analysis of the thermal-mechanical interaction between thrust force and drilling temperature revealed that the thermoplastic matrix glass transition temperature exerts a significant influence on cutting force. Elevated temperatures induce molecular chain disentanglement and slip in thermoplastic matrices, driving a glassy-elastic-viscous state transition. This transition produces continuous chips, contrasting with the powdery, discontinuous chips of CF/Epoxy.